2022
DOI: 10.3389/fcell.2022.884748
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell and single-nuclei RNA sequencing as powerful tools to decipher cellular heterogeneity and dysregulation in neurodegenerative diseases

Abstract: Neurodegenerative diseases affect millions of people worldwide and there are currently no cures. Two types of common neurodegenerative diseases are Alzheimer’s (AD) and Parkinson’s disease (PD). Single-cell and single-nuclei RNA sequencing (scRNA-seq and snRNA-seq) have become powerful tools to elucidate the inherent complexity and dynamics of the central nervous system at cellular resolution. This technology has allowed the identification of cell types and states, providing new insights into cellular suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 225 publications
0
14
0
Order By: Relevance
“…This has been confirmed by extensive AD research, as discussed in the following paragraphs. For a comprehensive overview of sc-/snRNA-seq AD studies without focus on astrocytes, refer to Cuevas-Diaz Duran et al ( 2022 ) and Saura et al ( 2022 ), or explore the scREAD database (Jiang et al, 2020 ).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…This has been confirmed by extensive AD research, as discussed in the following paragraphs. For a comprehensive overview of sc-/snRNA-seq AD studies without focus on astrocytes, refer to Cuevas-Diaz Duran et al ( 2022 ) and Saura et al ( 2022 ), or explore the scREAD database (Jiang et al, 2020 ).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Furthermore, increased microglial, endothelial cells, and oligodendrocytes population was observed in PD and other Lewy diseases 68,88 . Cortical regions exhibiting the most severe atrophy in symptomatic C9orf72, GRN and MAPT mutation carriers with FTD showed increased gene expression of astrocytes and endothelial cells 26 . Cortical thinning has been demonstrated to correlate with higher proportions of astrocytes, microglia, oligodendrocytes, oligodendrocyte precursor cells, and endothelial cells in cases of AD compared to controls 89 .…”
Section: Discussionmentioning
confidence: 92%
“…The invasive nature of expression assays, requiring direct access to neural tissue, and other numerous scaling limitations have impeded extensive spatial analyses 83 . Earlier studies, also using AHBA data, have shown that spatial patterns in gene expression and cell-type-specific genetic markers are associated with both regional vulnerability to neurodegeneration and patterns of atrophy across the brain 7,[23][24][25][26] . Since many neurodegeneration-related genes have similar levels of expression in both affected and unaffected brain areas 84 , characterizing changes in tissue loss associated with reference cell-type proportions in health may provide a clearer perspective on large-scale spatial patterns of cellular vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…Although several sources of information are available about the transcriptome of astrocytes under normal conditions (Batiuk et al, 2020; Boisvert et al, 2018; Clarke et al, 2018; Pan et al, 2020; Zhang et al, 2014) and in Alzheimer's disease (Diaz‐Castro et al, 2021; Forner et al, 2021; Galea et al, 2022; Habib et al, 2020; Liddelow et al, 2017; Rothman et al, 2018; Ruffinatti et al, 2018; Sadick et al, 2022; Simpson et al, 2011; Smith et al, 2022; Su et al, 2022), these data are not free from some experimental drawbacks (Cuevas‐Diaz Duran et al, 2022; Mattei et al, 2020). By using the laser‐capture technique, it was possible to obtain some information under less distorting conditions, but these studies did not correspond to hippocampal astrocytes (Merienne et al, 2019; Tagliafierro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%